Descriptive Analytical Study: Motivation, Perception And Consumer Preferences Towards Halal Packaging Among MSME Enterprises in Muhammadiyah Surabaya - Saputro, Andre Ridho; Putra, Andhika Cahyono; Sari, Meirna Dewita (Universitas Muhammadiyah Sidoarjo, 2025)
Muslim consumers' need for halal and sharia-compliant products continues to grow over time. The implication of this is an increase in demand for products with halal certificates. This research aims to reveal the motivations, perceptions and preferences of groups of entrepreneurs towards packaging products with halal certification. Data was obtained through a survey with a questionnaire to collect primary data from 100 respondents who were Muhammadiyah MSME business owners in Surabaya. The average analysis of research results shows that consumers' motivation to use halal packaging is mainly due to the need for quality packaging that is safe for use and according to religious law. Consumers perceive that halal packaging is guaranteed halal, quality and has an affordable price. Their level of preference is relatively high, consumers as entrepreneurs place halal packaging as the main choice and will use it continuously. Overall, the results of this research show that Muhammadiyah Surabaya business actors have quite positive motivations, perceptions and preferences for halal packaging. However, there is a need to increase awareness of the more attractive aspects of design as well as further education regarding the importance of innovation in halal packaging.